Controversial alternative diets in the light of current dietary recommendations for overweight and obesity treatment - Goral, Aleksander Karolina; Siwiela-Tomaszczyk, Justyna; Krzyszycha, Renata; Skrzypek, Michał (Polish Journal of Public Health, 2018)
The objective of the study is a critical analysis of the selected alternative diets used in the treatment of obesity inconsistent with the recommended standards, from the perspective of clinical dieticians, based on up-to-date guidelines for dietary management of obesity. Attention was paid to the assumptions of the selected alternative diets, some physiological mechanisms related with their use, as well as the deficit of data pertaining their distant effectiveness and safety. In the context of the current epidemiological situation concerning the prevalence of obesity, it is justifiable to undertake actions aimed at the professionalization of dietary management in obesity, consisting in the application of the treatment methods based on data generated in the EBM paradigm, with a simultaneous indication and criticism of dietary pseudo-therapies with unconfirmed curative value which, in addition, do not guarantee the reduction of the risk of metabolic complications of obesity.